Effects of the intrayear fluctuation in serum albumin levels on the prognosis of patients on hemodialysis: a six-center, 3-year observational study in Japan - Nanami Kida; Yuto Ohta; Satoki Kato; Akihito Kamoto; Sachiyo Mizuguchi; Hidetsugu Hikita; Kiyoshi Yoshida; Yoshiharu Tsubakihara (Renal Replacement Therapy)
Abstract Background Malnutrition and hypoalbuminemia are prognostic factors for mortality in patients undergoing hemodialysis (HD). We hypothesized that the monthly variability in albumin levels was a stronger prognostic factor than its baseline level. Therefore, in this study, we aimed to investigate the association between the 3-year prognosis and 1-year fluctuations in serum albumin levels of patients on HD. Methods In this retrospective follow-up study, we enrolled patients on HD from six centers between January 2014 and December 2014. Serum albumin levels were obtained every month during this period. We calculated the fluctuation rate of serum albumin levels using the following equation: (highest value – lowest value of the year)/average value of albumin during the year. We divided the patients into two groups on the basis of the median fluctuation rate. All patients were followed up from January 2015 to January 2017. The primary outcome of this study was all-cause mortality, and the secondary outcome was the combined endpoint of mortality and major cardio-cerebrovascular adverse events (MACCEs). Results Overall, 621 patients on HD were included in this study. The median rate of fluctuation in albumin levels in all patients was 14.5%. Compared with patients in the low fluctuation (LF) group (< 14.5%) (n = 308), those in the high fluctuation (HF) group (≥ 14.5%) (n = 313) were significantly older (67 versus 65 years; p = 0.009). During a mean follow-up period of 31.0 ± 10.1 months, there were 121 (19.5%) and 191 (30.5%) cases of all-cause death and combined endpoint, respectively. Kaplan–Meier analysis results showed that the HF group had a significantly worse prognosis in terms of all-cause mortality (log-rank test, p = 0.005) and combined endpoints (log-rank test, p = 0.001) than the LF group. Among patients with low albumin levels (< 3.7 g/dL), multivariate analysis results demonstrated that HF was independently associated with an increased risk of all-cause mortality and composite endpoint (hazard ratio [HR]: 1.02, 95% confidence interval [CI] 1.00–1.04, p = 0.011; HR: 1.02, 95% CI 1.00–1.03, p = 0.002). Conclusion In patients on HD, high fluctuations in serum albumin levels were significantly associated with increased all-cause mortality risk. Thus, attention should be paid not only to the monthly albumin level but also to its fluctuations.